Electrochemical properties enhancement of spinel lithium nickel manganese oxide by secondary heat treatment and assistant phase formation - Giang, Do Xuan; Tung, Mai Thanh (Vietnam Journal of Chemistry, 2015)
LiNixMn2-xOy as cathode materials discharge at 4.7 V versus Li+/Li potential produced high stability of structures during lithium insertion/extraction. The supplement of Ni amount of x > 0.5 appeared the secondary cubic phase of hexa-nickel Manganese Oxide which assisted the material increase the electrochemical performance. The additional heat treatment at 700 oC for 36 hours of two phases LiNi0.5Mn1.5O4 and Ni6MnO8 enhances cycle ability of entire materials.